Adverse effects of fluoride towards thyroid hormone metabolism - MZ, Enggar Abdullah Idris; Wihardja, Rosiliwati (Padjadjaran Journal of Dentistry, 2008)
An easily ionized fluoride compound like Sodium Fluoride (NaF) has been used thus far as a dental caries prevention substance. However, fluoride ions also have a negative effect because it is very toxic. Several types of research on the effect of fluoride on guinea pigs and human beings indicate the presence synthesis obstruction of T3 and T4 that causes declined production, known as hypothyroidism. Hypothyroidism condition may obstruct tissue growth process and metabolism so as to impact various body organ systems. Preventive efforts against hypothyroidism caused by fluoride include avoiding diffusible fluoride compound intake, like NaF, in a long run systemic use, whereas efforts to overcome fluoride intoxication include consuming food that is rich in calcium, vitamin D, and antioxidant.